2015
DOI: 10.1038/srep17719
|View full text |Cite
|
Sign up to set email alerts
|

Object size can influence perceived weight independent of visual estimates of the volume of material

Abstract: The size-weight illusion is the phenomenon that the smaller of two equally heavy objects is perceived to be heavier than the larger object when lifted. One explanation for this illusion is that heaviness perception is influenced by our expectations, and larger objects are expected to be heavier than smaller ones because they contain more material. If this would be the entire explanation, the illusion should disappear if we make objects larger while keeping the volume of visible material the same (i.e. objects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 16 publications
(16 reference statements)
1
41
0
Order By: Relevance
“…The size of an object is one feature that typically informs the brain about its weight (Buckingham & MacDonald, 2016;Flanagan, Bittner, & Johansson, 2008;Plaisier & Smeets, 2015): Larger objects are often heavier, and this is especially true of objects that comprise the same material. This expectation is inherently violated in the SWI, in that the objects vary in volume but not mass.…”
Section: Weight Associations and The Swimentioning
confidence: 99%
See 2 more Smart Citations
“…The size of an object is one feature that typically informs the brain about its weight (Buckingham & MacDonald, 2016;Flanagan, Bittner, & Johansson, 2008;Plaisier & Smeets, 2015): Larger objects are often heavier, and this is especially true of objects that comprise the same material. This expectation is inherently violated in the SWI, in that the objects vary in volume but not mass.…”
Section: Weight Associations and The Swimentioning
confidence: 99%
“…The results demonstrated that the distribution of mass within an object was a stronger predictor of perceived weight than was mass per se. Amazeen and Turvey argued that when their rods were wielded, the critical, action-relevant variable influencing weight perception was rotational inertia, rather than mass (see Plaisier &Smeets, 2015, andZhu, Shockley, Riley, Tolston, &Bingham, 2013, for results that are inconsistent with this proposal). In a similar manner, Zhu and Bingham (2011) demonstrated a tight coupling between the SWI and perception of the throwability of hand-held objects.…”
Section: Overview Of Theories Of the Swi And Other Weight Illusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 4 There are also variants of the size-weight illusion that approach the present result but do not imply the same consequences. For example, a single barbell-shaped object whose width (but not weight) can be physically adjusted may feel differently light or heavy depending on its size (Plaisier & Smeets, 2015), even though the same amount of material is seen. This phenomenon too may be viewed as "impossible" in some sense (since it is not physically possible for an object to get heavier simply by changing its shape -though it is possible for shape changes to produce differences in leverage and required lifting effort).…”
Section: Discussionmentioning
confidence: 99%
“…In this illusion, a smaller object is judged to be heavier than an equally-weighted large object (see for reviews Buckingham, 2014; Dijker, 2014; Saccone & Chouinard, 2019). To induce the illusion, differences in the sizes of the objects can be perceived visually, haptically (Buckingham, 2019; Ellis & Lederman, 1993) or even illusory (de Brouwer, Smeets, & Plaisier, 2016) and can be independent of object volume (Plaisier & Smeets, 2015).…”
Section: Introductionmentioning
confidence: 99%